EFFECT OF ULTRASOUND-GUIDED DIRECT VITAMIN D INJECTIONS INTO PARATHYROID GLANDS ON LABORATORY MARKERS AND SURVIVAL OF PATIENTS WITH REFRACTORY SECONDARY HYPERPARATHYROIDISM - R. P. Gerasimchuk; A. Yu. Zemchenkov (Вестник трансплантологии и искусственных органов, 2016)
Aim. To evaluate the effect of local vitamin D injections into parathyroid glands on laboratory markers and survival in refractory hyperparathyroidism. Materials and methods. A comparison of the dynamics of secondary hyperparathyroidism laboratory markers and survival was performed in 37 patients with local vitamin D injections into the parathyroid glands under ultrasound guidance and in 62 patients with PTH higher than 600 pg/ml without reduction in PTH levels by more than 10% during 6 months, who continued to receive available conservative therapy. The mean duration of follow-up for groups was 40.5 and 33.2 months, respectively.Results. In the local injection group (LIG) PTH level reduced by 347 ± 360 pg/ml (38%) during the first month after injection course, and by 214 ± 255 pg/ml (28%) between annual average levels before and after injection course, while in control group (CG) it rose by 84 ± 277 pg/ml (11%). In LIG phosphate level significantly reduced by 0.18 ± 0.24 mmol/l (9%) after injection course and annual average level did not change. In CG annual average phosphate level significantly rose by 0.15 ± 0.37 mmol/l (7%). Cumulative survival by Kaplan–Maier was significantly higher in LIG (p = 0.025). Differences in survival in univariate and multivariate Cox regression models were significantly associated only with the fact of local injections course (p =0.04 inboth models).Conclusion. In current clinical practice the application of ultrasound-guided local vitamin D injections into parathyroid glands in patients with refractory hyperparathyroidism leads to a better control over laboratory markers and to significantly improved survival.